The Influence of Internally Generated Revenue and Capital Expenditure on Regional Financial Independence in Regencies/Cities of North Sumatra Province in 2019-2023 - Siska Triendent Manurung; R Budi Hendaris (Majapahit Journal of Islamic Finance and Management, 2026)
This study analyzes fiscal dynamics at the subnational level by examining the relationship between internally generated revenue and capital expenditure and their implications for regional financial independence across regencies and municipalities in North Sumatra Province during the 2019–2023 period. Using a quantitative research design, the study relies on secondary fiscal data obtained from official financial balance reports published by the Ministry of Finance of the Republic of Indonesia. The empirical analysis is conducted using multiple linear regression after ensuring that all classical assumption requirements are satisfied. The findings indicate that internally generated revenue has a positive and statistically significant effect on regional financial independence, suggesting that stronger local revenue capacity enhances fiscal autonomy and reduces reliance on intergovernmental transfers. In contrast, capital expenditure shows a negative and significant relationship with regional financial independence, reflecting the long-term nature of returns from public investment in fixed assets and infrastructure. When examined simultaneously, both variables significantly explain variations in fiscal independence among local governments. These results highlight the importance of strengthening local revenue mobilization while improving the strategic allocation of capital spending. Achieving sustainable regional financial independence under a decentralized governance framework requires a balanced approach that aligns revenue generation with prudent expenditure management to support long-term regional development.